Reduced susceptibility of a Biomphalaria tenagophila population to Schistosoma mansoni after introducing the resistant Taim/RS strain of B. tenagophila into Herivelton Martins stream. - Daisymara Priscila de Almeida Marques (Public Library of Science (PLoS), 2014)
Studies performed in the last 30 years demonstrated that a strain of B. tenagophila from the Taim Biological Reserve is completely resistant to Schistosoma mansoni infection. This resistance to parasite infection is a dominant characteristic during crossbreeding with susceptible B. tenagophila strains. These experiments also identified a 350 bp molecular marker that is exclusive to the Taim strain and does not occur in other geographic strains of this snail species. The Taim strain (Taim/RS) of Biomphalaria tenagophila was bred on a large scale, physically marked and introduced into a stream in which previous malacological analyses had revealed the presence of only parasite-susceptible B. tenagophila. Samples of offspring captured 4, 11 and 14 months after the introduction of the Taim strain were examined, and the susceptibility of the snails to S. mansoni infection dropped from 38.6-26.5% to 2.1% during the 14 months after the introduction of the Taim snail strain. A significant correlation was also observed between the absence of infection and the identification of the Taim molecular marker. These results demonstrate that the genetic marker from the Taim strain was successfully introduced into the wild snail population. In addition, a significant relationship exists between the marker and resistance to infection.